Design of Monitoring and Control System For Air Temperature And Humidity In Oyster Mushroom Cultivation Room Based on IOT - Raffa Aulia Mutaqi; Milda Yuliza; Yul Antonisfia; Nisa Rahima Sakinah Nisa (International Journal of Wireless And Multimedia Communications, 2025)
Oyster mushroom cultivation is very popular among rural and urban communities, both on a small, medium and industrial scale. Oyster mushroom cultivation requires controlling the temperature and humidity in the mushroom barn to get optimal mushroom body growth. In general, the optimal temperature for oyster mushroom growth in the fruiting phase is 26-30°C with a humidity of 70-95%RH. This system describes the workings of the device used to monitor temperature and humidity using a DHT22 sensor through a microcontroller, which is displayed on the Blynk application and a 20x4 LCD. Measurements in lowland areas show a temperature of 29°C and humidity of 95%. The percentage error of the temperature measurement with the DHT22 sensor is 6.37%, with an average error of 1.60%. As for humidity, the measurement error is 0.71% with an average error of 0.82%. With this system, mushroom farmers can monitor the environmental conditions of the cultivation room in real-time through an IoT platform connected to the sensor.